Newborn intestinal occlusion: Jejunum-ileum small intestine atresia - Cabrera R. de Aguirre, Maria T. (Cirugía del Uruguay, 1979)
In studying jejuno - ileal atresia case - material available locally, considerable importance is attached to their evaluation according to Lester's classification, since prognosis is contingent on type. Idear surgery consists o'f. termino - terminal anastomosis and early diagnosis( preoperato;y and post - opJratory care in the adequate services is essential due to the necessity of para - enteric support. Consideration is also given to the problem of re - operations and their timeliness. Poor results are the consequence of: 1) Prematurity; 2) Atresia variety or a combination of (1) and (2); 3) Non - functional suture or dehiscence; 4) Failure to reoperate dilated loop syndrome or dehiscence at the right moment,; 5) Lack of absortion surface due to resection or everly - extensive atresia.